Optimal portfolio choice with predictability in house prices and transaction costs - Stefano Corradin; José L. Fillat; Carles Vergara-Alert (European Central Bank (ECB), 2012)
We generalize the classic Grossman and Laroque (1990) (GL) model of optimal portfolio choice with housing and transaction costs by introducing predictability in house prices. As in the GL model, agents only move to more expensive (cheaper) houses when their wealth-to-housing ratios reach an optimal lower (upper) boundary. However, in our model, these boundaries are time-varying and depend on the dynamics of the expected growth rate of house prices. We find that households moving to a more expensive house in periods of high expected growth in house prices have significantly lower ex-ante wealth-to-housing ratios than those moving in periods of low expected growth. We also find that the share of wealth invested in risky assets is lower during periods of high expected growth in house prices and that it is higher right before moving during periods of low growth. The main implications of the model are robust to tests using household level data from the PSID and SIPP surveys.
Keywords: G11; D11; D91; C61; 330; Durable goods; housing returns predictability; optimal housing consumption and investment; transaction costs